Instructional Film Research Program Period: 1 March to 30 June 1949. Progress Report Number 11-12. - Pennsylvania State Univ., University Park. Coll. of Education; Pennsylvania State Univ., University Park. Coll. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1949)
A combination of a progress report and a technical report, this paper should prove useful as an aid in planning future research, and should prove generally useful to those interested in communication processes by means of sound films, as well as to those who work in the areas of radio and television. Effectively there are two halves to the paper. The first half is classified into five parts, in terms of learning principles, of some areas for research on instructional films; and the second part, the appendix, comprises a summary of the experimental projects of the Instructional Film Research Program in relation to the foregoing classification which, specifically, is: 1. Psychological learning principles and their relationship to learning from films. 2. Film characteristics and their effect on learning. 3. Development of new equipment and procedures for testing instructional films. 4. Research on methods for utilizing films in instruction; and 5. Reviews of pertinent literature and theoretical systems. A skeleton classification of some areas for research on instructional films, which folds out for easy reference, is appended. (GO)
Sponsoring Agency: Office of Naval Research, Port Washington, NY. Special Devices Center.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Instruction; Educational Equipment; Educational Experiments; Films; Group Instruction; Literature Reviews; Media Research; Production Techniques; Repetitive Film Showings; Teaching Methods; Audiovisual Aids; Film Production; Film Study; Instructional Films; Learning Theories